2018
DOI: 10.9798/kosham.2018.18.5.119
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effective Methods of Securing the Golden Time of Fire Engine Move Out

Abstract: Statistics from the Fire Department illustrate that over the last five years, the rates for fire enforcement arriving within the Golden Time is on average only 60 %, and this is not a high enough safety rate. Golden Time has to be secured because it is directly related to saving lives, but at present, it is not working well. Fire engines would be capable of traveling within the Golden Time based on the following three factors: securing the fire engines, securing the emergency route, and the limitations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The uncertainty of re ghting duties has been shown to negatively affect job performance, sleep patterns, and social/familial relationships [11]; moreover, shift work-related circadian rhythm sleep-wake disorders can signi cantly impair mental and physical health [12]. Furthermore, the urgency of re ghting tasks to meet the golden hour for re ghting, rescue, and emergency medical activities can lead to circadian rhythm disruption and stress [13]. A systematic review on non-cancerous health risks among re ghters [14] found that re ghters have a higher risk of mental disorders, hearing impairment, myocardial infarction, and ischemic stroke than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty of re ghting duties has been shown to negatively affect job performance, sleep patterns, and social/familial relationships [11]; moreover, shift work-related circadian rhythm sleep-wake disorders can signi cantly impair mental and physical health [12]. Furthermore, the urgency of re ghting tasks to meet the golden hour for re ghting, rescue, and emergency medical activities can lead to circadian rhythm disruption and stress [13]. A systematic review on non-cancerous health risks among re ghters [14] found that re ghters have a higher risk of mental disorders, hearing impairment, myocardial infarction, and ischemic stroke than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Going forward, the findings of this study are expected to be applied to basic research aimed at establishing standards for placement of emergency firefighting equipment. (2) 지연되는 도착시간으로 인해 대 , 형화재로 확대되는 사례가 빈번히 발생하고 있다 (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the recommended time between fire vehicles leaving the garage and arriving at the scene for extinguishing, rescue, and first-aid operations is less than five minutes. However, the arrival time at the fire site is delayed due to traffic congestion and parking problems, resulting in frequent large-scale fires [2]. In general, the travel time of fire vehicles is affected by land-use behavior (residential, commercial, industrial, etc.…”
mentioning
confidence: 99%